Pidginitation of Bimanese at Seventh Grade of SMP Negeri 2 Bolo - Mira Anggriana; Ramli; Fitri Ningsi (CV. Eureka Murakabi Abadi, 2021)
This study discusses the pidginitation of bimanese at seventh grade SMPN 2 Bolo ,which aims to determine the types of communication pidgin , and to identify the effects contained in the pidgin. This study focuses on the theory of Trask L.A Then analyzed using qualitative descriptive methods. The researcher used the video and wrote text as in Whatsaap group to find out more data validity. This research was conducted to determine the types of communication functions inpidginitation. The findings show that the types of communication fuctions in pidgin actions are: 3 assertive (addition), 1 directives (lexifer), 3 expressive (lexicon) , declarations ( declaration not found in this study) ). Then, in the act of perlokusi. The researcher concluded that assertions and offer commintments were usually used by the pidgin. Based on the explanation above, the researcher concluded that the pidgin of pidginitation of effect of function communication pidgin ,Beijing 2014.